Miniature compact folded dipole for metal mountable UHF RFID tag antenna - Fuad Erman; Effariza Hanaf; Lim, Eng-Hock; Wan Amirul Wan Mohd Mahyiddin; Sulaiman Wadi Harun; Hassan Umair; Rawan Soboh; Mohamad Zul Hilmey Makmud (Multidisciplinary Digital Publishing Institute (MDPI), 2019)
This article describes the design of an Ultra-High Frequency (UHF) miniature folded dipole Radio Frequency Identification (RFID) tag antenna that can be mountable on metallic objects. The compact tag antenna is formed from symmetric C-shaped resonators connected with additional arms embedded into the outer strip lines for miniaturization purposes. It is loaded with outer strip lines, resulting in a flexible tuning method that is capable of matching the integrated circuit (IC) chip’s impedance. The proposed tag is fabricated on a single layer of Polytetrafluoroethylene (PTFE) substrate. It has simple structure and does not require any metallic vias or shorting plate. The miniature tag antenna with a size of 82.75 × 19.5 × 1.5 mm3 yields a total realized gain of −0.53 dB at the resonance frequency when attached to a 40 × 40 cm2 metal plate. The presented design utilizes a European RFID band, and the simulated results of realized gain, read range, and input impedance are verified with measurement results.